Trust, collaboration, and policy attitudes in the public sector - Philip Keefer; Sergio Perilla; Razvan Vlaicu (Inter-American Development Bank (IDB), 2021)
This paper examines new data on public sector employees from 18 Latin American countries to shed light on the role of trust in the performance of government agencies. We developed an original survey taken during the first COVID-19 wave that includes randomized experiments with pandemic-related treatments. We document that individual-level trust in coworkers, other public employees, and citizens is positively related to performance-enhancing behaviors, such as cooperation and information-sharing, and policy attitudes, such as openness to technological innovations in public service delivery. Trust is more strongly linked to positive behaviors and attitudes in non-merit-based civil service systems. High-trust and low-trust respondents report different assessments of their main work constraints. Also, they draw different inferences and prefer different policy responses when exposed to data-based framing treatments about social distancing outcomes in their countries. Low-trust public employees are more likely to assign responsibility for a negative outcome to the government and to prefer stricter enforcement of social distancing.
Keywords: D73; H83; 330; Trust; Cooperation; Policy attitudes; Public sector; Pandemic; Survey experiments